Legislación y políticas en Nueva Granada y Chile para atraer la inmigración extranjera a mediados del siglo XIX - Vicente Romero (Les Cahiers ALHIM)
In the middle of the 19th century, an exceptional number of Europeans went to the American continent, especially to United-States. Chile and New Granada States given same lows to attract a part of those Europeans into their countries. To reach this, the foreigners could obtain the status of nationals than before. Even if have censitary conditions, they would be active citizens. These south-American States take same resolutions in view to transform these migrants in owners in their country. However the State programs of colonization with foreigners actually were extremely discreet. Administration of those countries decided to install a reduced number of groups of foreigner migrants in traditionally eccentric regions of their country. Settled in these regions, it’s clear that those foreigners’ colonies will be an allied force of the State and the criolla dominant class, as avant-garde on the frontline in the aim to underpin the territory or conquer and colonize the lands ant Indian territories. By this way these foreigners’ colonies are not a threat but consolidate the traditional economic and social power in these countries. For the “coolie-Indians” and other kind of manual workers and day laborers that will arrive, those State programs envisage only a subaltern social destiny.